The effect of soursop leaf extract on pancreatic beta cell count and fasting blood glucose in male wistar rats exposed to a high-fat diet and streptozotocin - Astini, Dewa Ayu Agung Alit Suka; Gunawan, H Ari; Santoso, R Mochamad Wirono Aman; Andajani, Susilowati; Basori, Ahmad (Folia Medica Indonesiana, 2017)
Based on some researches known that soursop leaf extract can improve beta cell injury. The aims of this study was to analyze the effect of soursop leaf extract on fasting blood glucose (FBG) and pancreatic beta cell number in male Wistar rats wich were exposed to a high-fat diet and streptozotocin. This study design is the only randomized posttest control group design. The total sample size is 50 male Wistar rats. The independent variable: high-fat diet, STZ, and soursop leaf extract; the dependent variable: pancreatic beta cells number, and FBG3. Data tested for normality with Kolmogorov-Smirnov (a=0.05) and tested of homogeneity with Levene (a =0.05). Comparison test between groups with Kruskal-Wallis (a=0.05), followed by Mann Whitney. Correlation test with Pearson (a=0.05) between dose of the soursop leaf extract and FBG3, and between dose and the number of pancreatic beta cells. The results of this study showed that the soursop leaf extract at a dose of 100 mg/kg and 150 mg/kg have an effect on fasting blood glucose levels and panreatic beta cells number;2)There is a significant negative correlation between the orograstric lavage of soursop leaf extract with FBG3 (r=-0.647;p<0.001), the increasing doses of soursop leaf extract, further lowering fasting blood glucose levels;3)There is a significant positive correlation between the orograstric lavage of soursop leaf extract with the number of pancreatic beta cells (r=0,759;p<0,001), the increasing doses of soursop leaf extract, further increasing pancreatic beta cells number. In conclusion, increasing doses of soursop leaf extract, further lowering fasting blood glucose and increasing the number of pancreatic beta cells.